Imperfect knowledge, inflation expectations, and monetary policy - Athanasios Orphanides; John C. Williams (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
This paper investigates the role that imperfect knowledge about the structure of the economy plays in the formation of expectations, macroeconomic dynamics, and the efficient formulation of monetary policy. Economic agents rely on an adaptive learning technology to form expectations and to update continuously their beliefs regarding the dynamic structure of the economy based on incoming data. The process of perpetual learning introduces an additional layer of dynamic interaction between monetary policy and economic outcomes. We find that policies that would be efficient under rational expectations can perform poorly when knowledge is imperfect. In particular, policies that fail to maintain tight control over inflation are prone to episodes in which the public's expectations of inflation become uncoupled from the policy objective and stagflation results, in a pattern similar to that experienced in the United States during the 1970s. Our results highlight the value of effective communication of a central bank's inflation objective and of continued vigilance against inflation in anchoring inflation expectations and fostering macroeconomic stability.
urn:nbn:de:hebis:30-10458
Keywords: E52; 330; Imperfect Knowledge; Inflation Expectations; Monetary Policy; Inflationserwartung; Geldpolitik; Lernprozess; Inflation Targeting; Unvollkommene Information; Rationale Erwartung; Theorie